COOPERATION OF THE REPUBLIC OF KAZAKHSTAN IN THE FRAMEWORK OF THE SCO (Journal of Philosophy Culture and Political Science, 2018)
The Republic of Kazakhstan attaches great importance to cooperation within the framework of the Shanghai Cooperation Organization (SCO). For historical, socio-economic and political reasons, Kazakhstan is strategically interested in maintaining stability and development of both multilateral and bilateral relations with the republics of Central Asia.